2022
DOI: 10.1371/journal.pgen.1010525
|View full text |Cite
|
Sign up to set email alerts
|

A widespread inversion polymorphism conserved among Saccharomyces species is caused by recurrent homogenization of a sporulation gene family

Abstract: Saccharomyces genomes are highly collinear and show relatively little structural variation, both within and between species of this yeast genus. We investigated the only common inversion polymorphism known in S. cerevisiae, which affects a 24-kb ‘flip/flop’ region containing 15 genes near the centromere of chromosome XIV. The region exists in two orientations, called reference (REF) and inverted (INV). Meiotic recombination in this region is suppressed in crosses between REF and INV orientation strains such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 98 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…S1 ). Of interest, we detected the recently described recurrent inversion of 24 kb on Chr XIV ( Salzberg et al 2022 ); two strains had the reference orientation, and 14 strains had the inversion. We also detected a novel tandem repeat specific to strain YJM454 that amplified the uncharacterized open reading frame (ORF) YGR201C to 27 copies ( Supplemental Fig.…”
Section: Resultsmentioning
confidence: 86%
“…S1 ). Of interest, we detected the recently described recurrent inversion of 24 kb on Chr XIV ( Salzberg et al 2022 ); two strains had the reference orientation, and 14 strains had the inversion. We also detected a novel tandem repeat specific to strain YJM454 that amplified the uncharacterized open reading frame (ORF) YGR201C to 27 copies ( Supplemental Fig.…”
Section: Resultsmentioning
confidence: 86%
“…This flip/flop inversion region is flanked by two 4.2-kb inverted repeat (IR) regions and remains polymorphic in S . cerevisiae and its sister species in the genus Saccharomyces [17]. For example, within S. cerevisiae , our previous study revealed that the Sake strain Y12 shared conserved synteny with the S .…”
Section: Resultsmentioning
confidence: 99%
“…These WGAs were generated mostly with long-read sequencing data (PacBio or ONT), however we also included three WGAs generated with short-read sequencing data for S. cerevisiae that showed evidence of Tsu4 internal regions (strain 245 from (Marsit et al ., 2015); strains AFQ and CDM from (Peter et al ., 2018)) and two WGAs generated with short-read sequencing data for S. arboricola (strain H-6 from (Liti et al ., 2013) and strain ZP960 from (Peris et al ., 2023)) that represent the best available WGAs for this species. In total, we analyzed 183 S. cerevisiae WGAs (Marsit et al ., 2015; Yue et al ., 2017; Peter et al ., 2018; O’Donnell et al ., 2023), 12 S. paradoxus WGAs (Yue et al ., 2017; Eberlein et al ., 2019; Chen et al ., 2022b), two S. mikatae WGAs (this study), two S. jurei WGAs (Naseeb et al ., 2018), three S. kudriavzevii WGAs (Boonekamp et al ., 2018; Salzberg et al ., 2022), two S. arboricola WGAs (Liti et al ., 2013; Peris et al ., 2023), two S. uvarum WGAs (Chen et al ., 2022a; Salzberg et al ., 2022), and four S. eubayanus WGAs (Brickwedde et al ., 2018; Brouwers et al ., 2019; Mardones et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%